(untitled) (Journal of the College of Basic Education, 2022)
Criticism is one of the means of expressing the effectiveness of the grammatical lesson for linguists, as it was a realistic expression and a real translation of the linguistic and grammatical movement witnessed in the metropolises of Basra and Kufa, and from them to the Arab and Islamic countries, and it was the one that was attended by the councils of scholars. Before the emergence of criticism, the Arabs used to utter in their own way and what their voice suggested to them, their tongues did not falter in error, and the serenity of their words was not distorted by a melody. This melody paid off its danger, and one of the fruits of this thinking was the development of grammar and morphology rules that preserved the language for us from slippage. Hence the title of the research (The Grammatical Criticism of Expansion for the Kufics) because it sheds light on the philosophy of the Arabic language and tries to highlight some of its aspects after it suffered from darkness and loss. Tensi or abandonment of its vocabulary. The researcher divided the research into an introduction and three chapters with a conclusion. The first chapter dealt with the definition of criticism and its divisions. The second chapter was the subject of criticism of the expansion of the Kufis in terms of terminology and evidence, while the third chapter explained the criticism of analogy and accompanying the situation.. Keywords: